2017
DOI: 10.1021/acs.est.7b01299
|View full text |Cite
|
Sign up to set email alerts
|

HULIS Enhancement of Hydroxyl Radical Formation from Fe(II): Kinetics of Fulvic Acid–Fe(II) Complexes in the Presence of Lung Antioxidants

Abstract: Oxidative stress mediated by reactive oxygen species (ROS) is a hypothesized mechanism for particulate-matter related health effects. Fe(II) is a key player in ROS formation in surrogate lung fluid (SLF) containing antioxidants. Humic-like substances (HULIS) in particulate matter such as biomass burning aerosol chelate Fe(II), but the effect on ROS formation in the presence of lung antioxidants is not known. We use Suwanee River Fulvic Acid (SRFA) as a surrogate for HULIS and investigate its effect on OH forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 60 publications
4
85
2
Order By: Relevance
“…Similarly, Hems et al (2017) found that suppression of OH generation (photo-Fenton reaction) occurred, and attributed the decrease to the formation of metal-SOA complex. Although current studies demonstrate such metal-SOA binding leads to a lower OP, other studies (Gonzalez et al, 2017;Yu et al, 2018) have found an increased level of OH radicals through the formation of Fe (II)-HULIS complex. These synergistic/antagonistic metal-organic interactions are relevant to multiple health outcomes.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Similarly, Hems et al (2017) found that suppression of OH generation (photo-Fenton reaction) occurred, and attributed the decrease to the formation of metal-SOA complex. Although current studies demonstrate such metal-SOA binding leads to a lower OP, other studies (Gonzalez et al, 2017;Yu et al, 2018) have found an increased level of OH radicals through the formation of Fe (II)-HULIS complex. These synergistic/antagonistic metal-organic interactions are relevant to multiple health outcomes.…”
Section: Discussioncontrasting
confidence: 75%
“…) have been shown to be redox-active (Charrier and Anastasio, 2012;Xiong et al, 2017). Metals in ambient particles can range from insoluble substances to soluble cations, leading to var- ious health outcomes after deposition onto the human respiratory tract (Gojova et al, 2007;Oberdörster et al, 2005).…”
Section: Op Changes Upon Mixing With Cumentioning
confidence: 99%
“…(AA, d ai ) displayed the same dimensional profile at the two site: a negligible response below about 1 µm and a coarse mode (maximum at 3.2-5.6 µm), suggesting sensitivity toward redox active components in coarse aerosol, namely to redox active components released by brake abrasion, such as Cu and Fe, to whom OP AA assays is known to be sensitive [14,[27][28][29][30]. ( , ) and ( , ) displayed the same dimensional profile at the two site: a negligible response below about 1 μm and a coarse mode (maximum at 3.2-5.6 μm), suggesting sensitivity toward redox active components in coarse aerosol, namely to redox active components released by brake abrasion, such as Cu and Fe, to whom OP AA assays is known to be sensitive [14,[27][28][29][30].…”
Section: Aerosol Respiratory Doses From Biomass Burningmentioning
confidence: 82%
“…The differences between the two tests were evident in terms of total ( ) and ( ) doses as well. ( ) and ( ) were higher at the Ferrara than at the Rome site, whereas the contrary ( , ) and ( , ) displayed the same dimensional profile at the two site: a negligible response below about 1 μm and a coarse mode (maximum at 3.2-5.6 μm), suggesting sensitivity toward redox active components in coarse aerosol, namely to redox active components released by brake abrasion, such as Cu and Fe, to whom OP AA assays is known to be sensitive [14,[27][28][29][30].…”
Section: Oxidative Potential Respiratory Dosesmentioning
confidence: 87%
“…, and non-radical species such as O3 and H2O2 in the ELF 20 (Kelly and Fussell, 2017;Sies et al, 2017). Although quinones and TMs are widely recognized as being redox-active, other redox-active chemicals, such as those in humic-like substances, are also anticipated to pose OP (Charrier and Anastasio, 2012;Verma et al, 2015;Dou et al, 2015;Gonzalez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%